Information Product Analysis as An Effort to Improve The Library's Recreational Function - Agustine, Merryam; Rejeki, Diah Sri; Wahyuni, Haria Saputry (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2024)
The recreational function in libraries refers to the role that libraries play in providing recreational activities and resources for the community. Although libraries are traditionally associated with the storage and dissemination of knowledge, they also serve as important community centers that offer a range of recreational and entertainment services. The objectives of this study are to: (1) find out the types of information products that can be used to improve the recreational function of the library; (2) find out the user specifications of information products as an effort to improve the recreational function of the library; (3) find out the application areas of information products as an effort to improve the recreational function of the library. The research stages to be carried out are the preparation stage in the form of data collection through surveys and library data, the data processing stage, the data analysis stage, and the preparation of the final report. This research highlights the importance of diversifying library collections. A diverse collection can attract different types of patrons and better meet their recreational needs. This includes fiction, non-fiction books, multimedia, and digital resources. Additional services and facilities are needed. In addition to a diverse collection, research also shows that additional services and facilities, such as comfortable reading rooms, children's play areas, and recreational event programs, can enhance the appeal of libraries as recreational venues.